2014
DOI: 10.1364/ol.39.006923
|View full text |Cite
|
Sign up to set email alerts
|

Functional optical coherence tomography reveals transient phototropic change of photoreceptor outer segments

Abstract: Dynamic near infrared microscopy has revealed transient retinal phototropism (TRP) correlated with oblique light stimulation. Here, by developing a hybrid confocal microscopy and optical coherence tomography (OCT), we tested sub-cellular source of the TRP in living frog retina. Dynamic confocal microscopy and OCT consistently revealed photoreceptor outer segments as the anatomic source of the TRP. Further investigation of the TRP can provide insights in better understanding of Stiles–Crawford effect (SCE) on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…The methods employed for the quantification of ROS movements and the segmentation of active areas were as described previously [2]. An optical flow algorithm [18] was employed to generate a movement magnitude map (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods employed for the quantification of ROS movements and the segmentation of active areas were as described previously [2]. An optical flow algorithm [18] was employed to generate a movement magnitude map (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the previous and present studies differ in several respects, including the investigation of intact eye vs. isolated retina, OCT vs. microscopy system, and possible differences in photo stimulation efficiency, the extent to which the presently measured ROS movement accounts for the previously measured overall IOS remains to be determined. For isolated retina, this issue can be addressed in future work by using either a camera with higher frame acquisition rate, or other high-speed imaging techniques such as high-speed confocal [10, [20][21][22] or OCT [2,11] systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 These studies also revealed that photoreceptor IOSs had a rapid time course (<4 ms after onset of the light stimulus). 13,28 Transient retinal phototropism was reported to be one factor that generates photoreceptor IOSs, [31][32][33] but the IOS physiological source has not been accurately determined yet. Before pursuing clinical applications, it is necessary to establish the relationship between IOS distortions and eye diseases.…”
Section: Introductionmentioning
confidence: 99%